Assessment of the vitamin A fortification of peanut butter on middle-income and low-income Filipino families and consumers in Cebu city - Roa, Abigail Matidios; Francicso, Ma. Leonora dL. (2003)
ABSTRACT The study was conducted to assess the impact of vitamin A fortified peanut butter on selected low-income and middle-income Filipino families in Cebu City. A total of 110 respondents participated in the one-on-one survey, comprised of middle-income families (54%) and the low-income families (46%). Demographics and socio-economic status of respondents showed that majority of the respondents were between 20-50 years old. Most of the middle-income group earns between P15,000-P24,999 monthly while for the low-income group, 78.43% earns between P5,000-P9,900 monthly. Majority of the respondents who finished tertiary education came from the middle-income group. Children aged 4-16 were the top consumers of peanut butter and consumption averages between 0.5-20 tablespoons per week. Taste emerged as the major factor in buying peanut butter (77.97% for middle-income group and 70.59% for low-income group). Lady's choice was the most popular brand of peanut butter though most of the low-income families prefer homemade ones. Majority of both the middle and low-income families have heard and knows about vitamin A, 91.53% and 90.20% respectively. A greater number of the respondents (89.83% MI and 90.20% LI) were also aware that vitamin A fortified foods existed in the market however, there is low awareness specifically, of the existence of vitamin A fortified peanut butter (54.24% MI and 47.06% LI).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vitamin A; Peanut butter; Food, Enriched